The last juror - Grisham, John. (New York : Doubleday, 2004)
In 1970s Clanton, Mississippi, college dropout Willie Traynor turns a failed small-town paper into a success covering a local rape and murder case and finds his life coming full circle when the man convicted of that crime is paroled nine years after receiving a life sentence and jury members from the trial begin turning up dead.
Adult
Adult
Wilson's Fiction
Pub Weekly
New York Times
Keywords: Trials (Murder) -- Fiction; Newspaper publishing -- Fiction; Ex-convicts -- Fiction; Mississippi -- Fiction; Revenge -- Fiction; Jury -- Fiction; Trials (Homicide) -- Fiction; Newspaper publishing -- Fiction; Mississippi -- Fiction; Revenge -- Fiction; Jury -- Fiction; Legal stories; Mystery fiction; Suspense fiction; Legal stories